Evaluation of prediagnosis emergency department presentations in patients with active tuberculosis: the role of chest radiography, risk factors and symptoms. Issue 1 (17th January 2017) - Appleton, S C; Connell, D W; Singanayagam, A; Bradley, P; Pan, D; Sanderson, F; Cleaver, B; Rahman, A; Kon, O M
Abstract : Introduction: London has a high rate of tuberculosis (TB) with 2572 cases reported in 2014. Cases are more common in non-UK born, alcohol-dependent or homeless patients. The emergency department (ED) presents an opportunity for the diagnosis of TB in these patient groups. This is the first study describing the clinico-radiological characteristics of such attendances in two urban UK hospitals for pulmonary TB (PTB) and extrapulmonary TB (EPTB). Methods: We conducted a retrospective cohort study using the London TB Register (LTBR) and hospital records to identify patients who presented to two London ED's in the 6 months prior to their ultimate TB diagnosis 2011–2012. Results: 397 TB cases were identified. 39% (154/397) had presented to the ED in the 6 months prior to diagnosis. In the study population, the presence of cough, weight loss, fever and night sweats only had prevalence rates of 40%, 34%, 34% and 21%, respectively. Chest radiography was performed in 76% (117/154) of patients. For cases where a new diagnosis of TB was suspected, 73% (41/56) had an abnormal radiograph, compared with 36% (35/98) of patients where it was not. There was an abnormality on a chest radiograph in 73% (55/75) of PTB cases and also in 40% (21/52) of EPTB cases where a film was requested. Conclusions: A large proportion of patients with TB present to ED. A diagnosis was more likely in the presence of an abnormal radiograph, suggesting opportunities for earlier diagnosis if risk factors, symptoms and chest radiograph findings are combined.